DIAGNOSIS OF ACUTE PHARYNGITIS IN CHILDREN - T. V. Kulichenko; A. M. Kabaloeva; Yu. S. Lashkova; M. A. Lazareva (Педиатрическая фармакология, 2014)
This literature review is dedicated to the issue of clinical and laboratory diagnosis of acute pharyngitis in children and adolescents. Relevance of the topic is justified by omnipresent (up to 70% of patients with acute pharyngitis) unreasonable prescription of antibacterial drugs. Differential diagnosis of acute pharyngitis is aimed at identifying patients with the infection induced by group A-hemolytic streptococcus requiring antimicrobial therapy. The article presents current recommendations on microbial diagnosis of streptococcal tonsillitis and a potential of using express tests for rapid diagnosis verification.